Improvement of marine clay soil using lime and alkaline activation stabilized with inclusion of treated coir fibre - Kamaruddin, Fatin Amirah; Nahazanan, Haslinda; Kim Huat, Bujang; Anggraini, Vivi (MDPI, 2020)
Waste products have recently been used as one of the techniques in soil stabilization. The material is not just environmentally friendly, but also cheap. In this study, two different types of soil stabilizer—lime and alkaline activator (AA) with the inclusion of treated coir fibre as soil reinforcement in marine clay soil—were examined. The inclusion of fibre in the treated soil has had a positive impact in increasing the strength of the soil. Therefore, to assess the effectiveness of the soil treatment, mechanical tests such as indirect tensile strength, flexural test and unconfined compressive strength test were performed at three different curing periods (7, 28 and 90 days) on both untreated and treated soil. From the results, the inclusion of fibre in both lime and alkaline activation indicates an enhancement on post-peak behaviour from brittle to more ductile. Microstructural analyses of Field Emission Scanning Electron Microscope (FESEM) and Energy Dispersive X-ray (EDX) were also conducted after shearing to evaluate the changes of the soil before and after the treatment. Overall, results indicate that the treatment transformed the structure of the soil to become denser where it filled the large pores compared to untreated soil.